Diagnosis and management of soil fertility constraints in coconut (Cocos nucifera) : A review - MALHOTRA, S K; MAHESWARAPPA, H P; SELVAMANI, V; CHOWDAPPA, P (The Indian Journal of Agricultural Sciences, 2017)
Coconut (Cocos nucifera L.) is an important perennial plantation crop and to improve the productivity, the innate soil constraints should be ameliorated. The red, lateritic and sandy coconut soils are suffering with soil acidity, low CEC and poor nutrient reserve. A study on nutrient removal by coconut provides guidelines for the fertilizer input required. The effect of soil nutrient imbalance on the availability of nutrients emphasize the need based balanced fertilizer supply to coconut soils. The built up of soil available P in acidic red soils under continuous phosphatic fertilizer application strengthens the need to realize the soil test based fertilizer application. The potassium supply in the acid soils is poor, coconut being a huge feeder of potassium needs constant supply of potassium. Secondary and micronutrient deficiencies are emerging as potential yield limiting nutrients for coconut. Biomass recycling studies under coconut based cropping systems shows promising results in achieving the nutrient supply with the available biomass recycling through vermicompost. Minimizing the biomass exported out of farm especially coconut husk may improve potassium supply to palms through organic farming. Microbial studies showed that biomass recycling improved the beneficial microorganism in the rhizosphere and thereby enhances the nutrient availability. Fertigation technique showed higher nutrient use efficiency, soil and water conservation measures improved the yield of coconut in sandy soil and checks the losses through run-off and erosion in sloppy soils. Site specific soil management strategies can improve the coconut yield in an eco-friendly way.